Wrightite, K2Al2O(AsO4)2, a new oxo-orthoarsenate from the Second scoria cone, Northern Breakthrough, Great Fissure eruption, Tolbachik volcano, Kamchatka peninsula, Russia. (15th May 2018) - Shablinskii, Andrey P.; Filatov, Stanislav K.; Vergasova, Lidyua P.; Avdontseva, Eugeniya Yu.; Moskaleva, Svetlana V.
ABSTRACT: The new mineral wrightite, K2 Al2 O(AsO4 )2, was found in 1983 at a fumarole on the Second scoria cone, Northern Breakthrough, Great Fissure eruption, Tolbachik volcano, Kamchatka peninsula, Russia, where it occurs as light yellow aggregates of transparent tabular crystals, with an average size of 0.05 mm × 0.03 mm × 0.005 mm. Wrightite is orthorhombic, space group Pnma, with the unit-cell parameters a = 8.230(5), b = 5.555(4), c = 17.584(1) Å, V = 803.9(6) Å 3 and Z = 4 (from powder data). The empirical formula is (K1.69 Na0.38 )Σ2.07 (Al1.80 Fe0.24 )Σ2.04 As1.96 O9 . The crystal structure ( R 1 = 0.043) consists of Al2 O(AsO4 )2 layers in the ab plane with clusters of edge-sharing AlO6 octahedra. Each layer contains two independent isolated AsO4 tetrahedra and two AlO6 octahedra. AlO6 octahedra are linked by edges, forming zigzag chains along the b axis inside the Al–As layer. Eight- and six-coordinated K atoms are located in the interlayer space between Al2 O(AsO4 )2 layers. The mineral is biaxial (−), α =1.679(2), β =1.685(2), γ (calc.) =1.687; 2V(meas.) = 62(10)° (λ = 589 nm). The strongest lines in the powder X-ray diffraction pattern [ d, Å( I )( hkl )] are: 8.77(36)(002); 4.458(17)(111); 4.010(19)(201, 013); 3.875(19)(104) and 2.972(100)(015). The mineral was named in honour of Adrian Carl Wright, Emeritus Professor at the University of Reading, UK.